Novel Approaches for Overcoming Biological Barriers - Agrahari, Vibhuti; Kumar, Prashant (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The human body poses various biological barriers to protect itself from pathogens, foreign materials and is important for its functioning and development. This reprint serves as a collection of research and review articles describing novel approaches and new therapeutic modalities to overcome biological barriers. This collection is a must read for scientists working in the field of drug and vaccine delivery.